Exploring Experiences of Digital Technology Integration in Social Learning: A Qualitative Case Study - Sandi, Aprilla; Linur, Rahmat; Yusron, Ali (el-Khuwailid: Journal of Multidisciplinary Studies, 2025)
Digital technology has provided innovative alternatives for delivering social learning materials more engagingly and effectively. Thus, this study employs a qualitative approach with a case study method to understand how students and teachers perceive and make sense of digital technology integration in social learning. Data were collected through in-depth interviews, observations, and document analysis. The participants include teachers and high school students actively using digital technology in social learning. Our finding reveals that the participants reported experiencing greater engagement in social learning with digital technology integration. Teachers and students also described technology integration as meaningful for their learning processes, such as understanding social concepts and fostering critical thinking and teamwork skills. However, this study also identifies several challenges in implementing digital technology, such as limited access to devices and the internet, teachers’ readiness to adopt technology, and difficulties managing digital distractions among students. In conclusion, digital technology integration could be an innovative solution to support more interactive and meaningful social learning when implemented with a more systematic and inclusive approach.